Associations of dietary patterns and pre-eclampsia: a matched case–control study. Issue 2 (6th May 2022) - Zhu, Yongjian; Liu, Yanhua; Fu, Wenjun; Zeng, Fangfang; Cao, Yuan; Dou, Weifeng; Duan, Dandan; Chen, Yuming; Lyu, Quanjun; Zhao, Xianlan
Abstract: Little is known about the effects of dietary patterns on prevalent pre-eclampsia in Chinese population. This study aimed to investigate the associations between dietary patterns and the odds of pre-eclampsia among Chinese pregnant women. A 1:1 age- and gestational week-matched case–control study was conducted between March 2016 and February 2019. A total of 440 pairs of pre-eclampsia cases and healthy controls were included. Dietary intakes were assessed by a seventy-nine-item FFQ and subsequently grouped into twenty-eight distinct groups. Factor analysis using the principal component method was adopted to derive the dietary patterns. Conditional logistic regression was used to analyse the associations of dietary patterns with prevalent pre-eclampsia. We identified four distinct dietary patterns: high fruit-vegetable, high protein, high fat-grain and high salt-sugar. We found that high fruit-vegetable dietary pattern (quartile (Q)4 v . Q1, OR 0·71, 95 % CI 0·55, 0·92, P trend = 0·013) and high protein dietary pattern (Q4 v . Q1, OR 0·72, 95 % CI 0·54, 0·95, P trend = 0·011) were associated with a decreased odds of pre-eclampsia in Chinese pregnant women. Whereas high fat-grain dietary pattern showed a U-shaped association with pre-eclampsia, the lowest OR was observed in the third quartile (Q3 v . Q1, OR 0·75, 95 % CI 0·57, 0·98, P trend = 0·111). No significant association was observed for high salt-sugar dietary pattern. In conclusion, pregnancy dietary pattern characterised by high fruit-vegetable or high protein was found to be associated with a reduced odds of pre-eclampsia in Chinese pregnant women.